Multiple body injuries in the data files of Emergency Actions of Specialist (ALS) teams - Januszewski, Juliusz (Polish Journal of Public Health, 2010)
Introduction. Multiple body injuries victims need professional medical aid in the place of accident and therefore resuscitation ambulances (with ALS teams) are essential to medical emergency service. Aim. The aim of the study was to assess the epidemiological data and procedures performed by the rescue team on-site of accidents. Material and methods. It was made the epidemiological analysis of protocols from actions took by rescue team during following years 2005 – 2008. The Abbreviated Injury Scale (AIS) and Injury Severity Score (ISS) were introduced to valuate injury grade. Results. The rescue team took 11,200 actions including 1,539 accidents (13.7%), of which 73.8% patients were transported to hospital treatment. Males were more frequent (993 – 64.5%), average 43 years old. Women victims over 65 years of age more often need help. Accidents had happened more often in June, August and December, and on Thursdays and Fridays. Cardiopulmonary resuscitation has been introduced to 3.4% of victims; decease as a consequence of accident was found to 4.8%. Prevailing traffic accidents (41.1%). Isolated body injuries were recognized at 73.6% with ISS 4,1, multiple body injuries at 4.9% with ISS 43.3, multi organ injuries at 3.8% with ISS 39.7 and plurilocular injuries at 17.7% with ISS 5.2. Multiplied body injuries were diagnosed by 4.9%, ISS was 43,4, caused more often need of resuscitation (57.4%) and deaths (36%). Detailed analysis proved that undertaken procedures were: dressing – 54.3%, pain relieve drugs – 53.1%, oxygen – 39.4%, fluids – 39%, immobilizing – 25.5%, monitoring – 11%. Abuse was found to 20% of victims. Conclusions. The study showed traffic and home accidents were the most frequent cause of injuries. The study marks the monthly temporariness of departures to incidents more often in June, August and December and week’s more often on Thursdays and on Fridays. The coefficient of accident rate carried out 122.5 on hundred thousand per year and for multiple body injuries victims 6 on hundred thousand per year. Multiple body injuries were recognized to 75 accidents victims, that was 5% of all patients, 47 of them were transported to hospital after introducing medical procedures on field, but 28 died. The victims with multiply body injuries always needed folded medical procedures including advanced live support that was introduced more often and were sufficient for save transportation to hospital.